England, Scotland and Europe: the Problem of the Frontier. (December 1975) - Hay, D.
Abstract : In what follows I propose to discuss certain questions concerning frontiers as they affect historians. Most of my time will be devoted to the Anglo-Scottish frontier, for the reason that it displays phenomena much more easily identified and documented than those associated with the frontiers of Europe. Some of the lessons one may draw from Anglo-Scottish frontier history are, moreover, of relevance elsewhere within the Continent, not only between countries but in some instances inside countries.